Object-oriented programming using C++ - Farrell, Joyce (Course Technology, 1998)
This text offers task-driven tutorials to guide intermediate-level programmers in the planning and creation of object-oriented programs. It is ideal for students who have had one previous C or C++ programming course, but does provide a review of the core C and C++ concepts. The realistic problems encountered in the running case scenario provide motivation for learning each new concept and technique. Each tutorial is divided into two lessons that introduce key concepts, guide students step by step through exercises, and reinforce the information with a summary, review questions, and additional exercises. The book is not written to a specific compiler, so students can use whichever compiler they are familiar with to build their programming skills. Each tutorial begins with a programming-related case problem that users can reasonably expect to encounter in business, followed by a demonstration of the applet they will create in the tutorial to solve that problem. Each tutorial is organized into two lessons - A and B - which introduce the concepts and techniques used in the completed application. A review section at the end of each self-contained lesson offers a convenient break point and enables students to test their understanding as they progress through the tutorial. Extensive end-of-chapter questions and hands-on activities reinforce material covered in the chapter; stand-alone programming projects and debugging exercises round out the programming skills. Appropriate for students with prior C or C++ programming experience. An overview reviews topics the student should already know.